1997
DOI: 10.3758/bf03199084
|View full text |Cite
|
Sign up to set email alerts
|

Pavlovian appetitive discriminative conditioning inAplysia californica

Abstract: Three experiments demonstrated Pavlovian appetitive discrimination learning in the marine mollusc, Aplysia californica. In each experiment, subjects were exposed to two conditioned stimuli; one stimulus (CS+) was paired with food presentations and the other stimulus (CS-) was never followed by food. In Experiments 1 and 3 different chemosensory stimuli were used, and in Experiment 2 different tactile stimuli were used. For both types of conditioned stimuli, bite responses occurred significantly more often to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Prior to any conditioning, these chemosensory stimuli elicit overt and conspicuous behaviors, such as feeding and disruption of escape locomotion (e.g., Figure 4C in Walters, Carew, & Kandel, 1979). Food (solid or extract) has been used as an US to condition feeding responses to other CSs-typically, novel chemical or tactile stimuli (Audesirk et al, 1982;Colwill et al, 1997;Kemenes & Benjamin, 1989;Mpitsos & Davis, 1973)-and to countercondition a preference for an innately aversive odor in Limax (Sahley et al, 1990). In short, food extracts are powerful stimuli that affect multiple sensory, motivational, and behavioral systems in gastropod molluscs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to any conditioning, these chemosensory stimuli elicit overt and conspicuous behaviors, such as feeding and disruption of escape locomotion (e.g., Figure 4C in Walters, Carew, & Kandel, 1979). Food (solid or extract) has been used as an US to condition feeding responses to other CSs-typically, novel chemical or tactile stimuli (Audesirk et al, 1982;Colwill et al, 1997;Kemenes & Benjamin, 1989;Mpitsos & Davis, 1973)-and to countercondition a preference for an innately aversive odor in Limax (Sahley et al, 1990). In short, food extracts are powerful stimuli that affect multiple sensory, motivational, and behavioral systems in gastropod molluscs.…”
Section: Discussionmentioning
confidence: 99%
“…Consider studies by Colwill and colleagues (Colwill et al, 1988;Colwill, Goodrum, & Martin, 1997), who have presented strong evidence for context discrimination learning by Aplysia. In an aversive context-conditioning study using two distinct environments that differed in substrate texture, shape, chemosensory composition, and other cues, Colwill et al (1988) administered a series of electric shocks in one context (CSϩ), but not in the other (CSϪ).…”
Section: The Combined Effects Of Differential Habituation Sensitizatmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylergonovine (1 nM) blocked the pairing-specific increase in fictive feeding that is usually induced by in vitro classical conditioning. The present results and previous observation that methylergonovine also blocks the effects of contingent reinforcement in an in vitro analog of appetitive operant conditioning suggest that DA mediates reinforcement for appetitive associative conditioning of feeding in Aplysia.The feeding behavior of Aplysia californica provides an attractive model system for investigating the cellular and molecular mechanisms underlying associative learning (see Susswein and Schwartz 1983;Colwill et al 1997; Elliot and Susswein 2002;Katzoff et al 2002;Brembs 2003;Brembs et al 2004;Cropper et al 2004). For example, aspects of feeding behavior (i.e., biting) can be modified by appetitive classical conditioning (Colwill et al 1997;Lechner et al 2000a); the isolated nervous system readily generates fictive feeding patterns (see Church and Lloyd 1994;Nargeot et al 1997); neural correlates of conditioning can be identified and studied in the isolated nervous system (Lechner et al 2000b;Lorenzetti et al 2004); and in vitro analogs, which are amenable to cellular and molecular analyses, recapitulate behavioral and neural changes that follow in vivo training (Mozzachiodi et al 2003;Brembs et al 2004;Lorenzetti et al 2004).…”
mentioning
confidence: 99%
“…For example, aspects of feeding behavior (i.e., biting) can be modified by appetitive classical conditioning (Colwill et al 1997;Lechner et al 2000a); the isolated nervous system readily generates fictive feeding patterns (see Church and Lloyd 1994;Nargeot et al 1997); neural correlates of conditioning can be identified and studied in the isolated nervous system (Lechner et al 2000b;Lorenzetti et al 2004); and in vitro analogs, which are amenable to cellular and molecular analyses, recapitulate behavioral and neural changes that follow in vivo training (Mozzachiodi et al 2003;Brembs et al 2004;Lorenzetti et al 2004). Several lines of evidence indicate that the esophageal nerve (En) mediates the effects of the unconditioned stimulus (US) during appetitive classical conditioning.…”
mentioning
confidence: 99%